Reducing Hinge Flexibility of CAR-T Cells Prolongs Survival In Vivo With Low Cytokines Release - Zhang, Ang; Sun, Yao; Du, Jie; Dong, Yansheng; Pang, Honggang; Ma, Lei; Si, Shaoyan; Zhang, Zhong; He, Mingyi; Yue, Yang; Zhang, Xiaoli; Zhao, Weichao; et al. (Frontiers in Immunology, 2021)
Abstract Chimeric antigen receptor (CAR)-modified T cells targeting CD19 demonstrate unparalleled responses in B cell malignancies. However, high tumor burden limits clinical efficacy and increases the risk of cytokine release syndrome and neurotoxicity, which is associated with over-activation of the CAR-T cells. The hinge domain plays an important role in the function of CAR-T cells. We hypothesized that deletion of glycine, an amino acid with good flexibility, may reduce the flexibility of the hinge region, thereby mitigating CAR-T cell over-activation. This study involved generating a novel CAR by deletion of two consecutive glycine residues in the CD8 hinge domain of second-generation (2nd) CAR, thereafter named 2nd-GG CAR. The 2nd-GG CAR-T cells showed similar efficacy of CAR expression but lower protein flexibility, and its protein affinity to CD19 protein was lower than that of 2nd CAR-T cells. Compared to the 2nd CAR-T cells, 2nd-GG CAR-T cells reduced proinflammatory cytokine secretion without diminishing the specific cytotoxicity toward tumor cells in vitro. Furthermore, 2nd-GG CAR-T cells reduced the tumor burden and prolonged overall survival in an immunodeficient mouse model bearing NALM-6, especially when tumor burden was high. This study demonstrated that a lower-flexibility of CD8α hinge enhanced antileukemic responses and reduced proinflammatory cytokines in preclinical studies. More broadly, it demonstrated the potential for modulating CAR functionality by changing the flexibility of the hinge domain, to enhance the safety and efficacy of CAR T cells in clinical settings.